(untitled) (Dhaka University Journal of Science, 2025)
This study aims to identify the potential determinants associated with teenage pregnancy in Bangladesh utilizing the Bangladesh Demographic and Health Survey (BDHS), 2017-18 clustered dataset. Random frailty term has been taken into account with the survival regression model to analyze the clustered data sets. Findings of this study have identified division, education of women and their partners, religion, working status, women’s autonomy, and spousal age difference to be potential factors affecting women to experience pregnancy during adolescence age. Dhaka Univ. J. Sci. 73(1): 13-18, 2025 (January)